Effects of crop spacing on weed competition and seed yield in cowpea, Vigna unguiculata [L.] Walp c.v. Ife Brown - Fadayomi, O. (Faculty of Agriculture, University of Ife, 2015)
When cowpea (Vigna unguiculnta [L.] Walp c.v. "Ife Brown") was planted at spacings of 50cm x 25cm and 50cm x 50cm. 31 and 15 percent yield increases were obtained over that of the conventional (100cm x 30cm spacing respectively Optimum yield was obtained under the 50cm x 25cm spacing with 4 weeks of weed-free maintenance, whereas 6 weeks of weed-free maintenance were required for the same under the 50cm x 50cm and 100cm x 30cm spacings. When weeds were allowed to compete with the crop for more than 4 weeks, yields decreased under the 50cm x 50cm and 100cm x 30cm spacings but yield reductions were not observed under the 50cm x 25cm spacing even with up to 6 weeks of weed competition.